Influence of skeletal maturity on size, function and sport-specific technical skills in youth soccer players - Gouvea, M.; Cyrino, E. S.; Ribeiro, A. S.; da Silva, D. R. P.; Ohara, D.; Valente-dos-Santos, J.; Coelho e Silva, M. J.; Ronque, E. (International Journal of Sports Medicine, 2016)
This study compared variation in size, function and sport-specific technical skills of youth soccer players associated with differences in biological maturity status. 60 male soccer players of under-14 (U14) and under-17 (U17) categories were submitted to anthropometric and body composition measurements as well as motor and soccer-specific technical skill tests. Skeletal maturity was determined by skeletal age. Athletes of both categories were classified as early, on-time or late-maturing, according to the difference between chronological age and skeletal age. Body mass and height were lower in the late athletes, independent of category (P<0.01). Differences in adiposity were found only between athletes of the U14 (late<early, P<0.05). Statistically significant differences were identified on aerobic endurance in U14 (early<on time, P<0.01), upper limbs muscular strength (late<early, P<0.01) and flexibility in U17 (late<on time, P<0.05). Players in each age group of contrasting maturity status do not differ in soccer-specific skills. The results suggest that the maturational development influences body mass, height, body fat, flexibility, muscular strength of upper limbs and cardiorespiratory fitness, whereas the specific technical skills and other functional capabilities do not seem to be affected.